Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy easy to activate and preparation method thereof

By adding Y, Mn, Zr, Co and Zn to the Ti-Fe-based hydrogen storage alloy and using mechanical ball milling technology to form a multiphase and nanocrystalline structure, the problems of high difficulty in alloy activation and poor hydrogen absorption and discharge performance are solved, and efficient hydrogen storage performance is achieved.

CN119592841AActive Publication Date: 2025-03-11CHINA IRON & STEEL RESEARCH INSTITUTE GROUP CO LTD

Patent Information

Application Number
CN202411706126.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-11
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing Ti-Fe-based hydrogen storage alloy has high activation difficulty, long activation cycle, poor hydrogen absorption and discharge kinetic performance, especially the defects of platform pressure drop and inclination.

Method used

By adding rare earth elements Y, transition metals Mn, Zr, Co and Zn to the Ti-Fe-based alloy, a multiphase structure and nanocrystalline structure are formed, and the microstructure is improved by using mechanical ball milling technology to simplify the activation process.

Benefits of technology

The alloy is easily activated, high hydrogen storage capacity and good hydrogen absorption and discharge performance. Activation can be completed at one time under 30℃ and 3MPa conditions, with hydrogen storage capacity ≥1.69wt.%, hydrogen absorption pressure ≥0.39MPa, and hydrogen release pressure ≥0.3MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592841A_ABST
    Figure CN119592841A_ABST
Patent Text Reader

Abstract

The invention relates to an easily-activated Ti-Fe-Y-Mn-Zr-Co-Zn-based hydrogen storage alloy and a preparation method thereof, belongs to the technical field of hydrogen storage alloy materials, and solves at least one of the problems of high activation difficulty, long activation period, poor hydrogen absorption and desorption dynamic performance and the like of a Ti-Fe-based hydrogen storage alloy in the prior art. The invention provides a Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy easy to activate, the chemical formula of the hydrogen storage alloy is Ti 1.15, Fe 0.8, Y 0.03, Mn 0.35-x-y-z ZrxCoyZnz, x, y and z are atomic ratios, x is larger than or equal to 0.05 and smaller than or equal to 0.15, y is larger than or equal to 0.02 and smaller than or equal to 0.1, and z is larger than or equal to 0.02 and smaller than or equal to 0.1. The Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy provided by the invention obtains good activation performance and hydrogen absorption and desorption performance by means of component design and preparation process improvement, can be activated at one time under the conditions of 30 DEG C and 3 MPa, and has the hydrogen storage capacity of more than or equal to 1.69 wt.%, the hydrogen absorption platform pressure of more than or equal to 0.39 MPa and the hydrogen desorption platform pressure of more than or equal to 0.3 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage alloy materials, and in particular to an easily activated Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy and a preparation method thereof. Background Art

[0002] TiFe intermetallic compounds can store large amounts of hydrogen (about 1.9wt.% H2) at room temperature and relatively low pressure. High-density TiFe hydrides have been used in many fields. This AB-type compound usually requires an activation procedure to absorb hydrogen for the first time, especially when it is produced by melting (induction furnace or arc furnace). Usually, this activation process includes a slow and complex heat treatment cycle, alternating heating with high temperature and cooling, and high-pressure hydrogen in a high vacuum.

[0003] The modification methods of TiFe alloy include partial replacement of Fe or Ti with one or several elements, chemical surface modification, mechanical alloying, etc. Studies have shown that mechanically alloyed TiFe can be simply activated, however, due to the appearance of amorphous phase, the hydrogen storage capacity becomes poor; surface modification can promote the hydrogenation of the material by catalyzing the dissociation and chemical adsorption of hydrogen molecules with a certain transition metal or alloy deposited on the surface, or eliminating the stable oxide layer with acid or alkali. These means also help to improve the anti-poisoning ability of TiFe alloy. Among these methods, element substitution is considered to be the most feasible, and a lot of research has been carried out. When Fe is partially replaced by Ni, Co, Al, V, Pd, Mn or Cr, the activation rate of the alloy is higher. In the case of adding Mn, it was found to be very effective in improving the activation characteristics and increasing the permeability to impure gases. However, this substitution will lead to a decrease in the platform pressure and a more inclined platform area, which is not conducive to the development of hydrogen storage devices and proton exchange membrane fuel cells.

[0004] In addition to improving the formula of hydrogen storage materials, people have also explored the processing methods of hydrogen storage alloys. After ball milling for 20 to 30 hours under Ar gas protection, TiFe alloy containing a small amount of Ni has good hydrogen absorption performance and is easy to activate or even does not require activation. However, the ball milling time is too long, which is not conducive to large-scale production. In addition, some researchers have observed that the yield loss is as high as 40% after 40 hours of ball milling. Summary of the invention

[0005] In view of the above analysis, the embodiments of the present invention aim to provide an easily activated Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy and a preparation method thereof, so as to solve at least one of the problems in the prior art of Ti-Fe based hydrogen storage alloys, such as high difficulty in activation, long activation cycle, poor hydrogen absorption and desorption kinetics (especially the defects of platform drop and tilt).

[0006] The present invention provides an easily activated Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy, wherein the chemical formula of the hydrogen storage alloy is Ti 1.15 Fe 0.8 Y 0.03 Mn 0.35-x-y-z Zr x Co y Zn z , where x, y, z are atomic ratios, and 0.05≤x≤0.15, 0.02≤y≤0.1, 0.02≤z≤0.1.

[0007] Preferably, it is characterized in that x:y:z=0.1:0.05:0.05.

[0008] Specifically, the hydrogen storage alloy includes a multiphase structure, including a TiFe phase and an intermetallic compound ZrMn2 phase, and the proportion of the ZrMn2 phase is 10-15% of the TiFe phase.

[0009] Specifically, Y exists in a free state, and Co and Zn are solid-dissolved in the TiFe phase.

[0010] Specifically, the hydrogen storage alloy has a nanocrystalline structure, and an average grain size is 15 to 35 nm.

[0011] The present invention also discloses a method for preparing the hydrogen storage alloy, comprising the following specific steps:

[0012] S1: The ingredients are prepared according to the preset chemical formula, wherein a certain proportion of the burn loss is added when weighing Mn, Zn and rare earth Y;

[0013] S2: Place the prepared raw materials in a zirconia crucible in order, place the pure iron rod vertically along the crucible wall, place the block rare earth Y at the bottom of the crucible, place the sponge Ti and Zr above the rare earth, and place the electrolytic Mn, Co and Zn on the sponge Ti and Zr;

[0014] S3: After the materials are placed in order, the furnace cover is closed, and after vacuuming, pure argon is filled in as a protective gas and heated to obtain a molten liquid master alloy, which is kept warm in a molten state and poured into a copper casting mold to obtain a master alloy ingot;

[0015] S4: After the master alloy ingot is mechanically crushed and sieved, the alloy powder under the sieve is loaded into a stainless steel ball mill together with stainless steel grinding balls, and then vacuumed and filled with high-purity argon gas. After ball milling in an omnidirectional planetary high-energy ball mill, a ball-milled alloy powder, i.e., the hydrogen storage alloy, is obtained.

[0016] Specifically, the burn-off amount of Mn, Zn and rare earth Y in step S1 is 5% to 10%.

[0017] Specifically, the specific process and parameters of step S3 are:

[0018] After the furnace cover is closed, vacuum is drawn to 1×10 -2 ~5×10 -5 Pa, fill with pure argon to 0.01-0.1 MPa, the melting temperature is 1500-1650°C, the melting and heat preservation time is 3-10 minutes, and the heat preservation time is preferably 5-8 minutes.

[0019] Specifically, in step S4, a 200-mesh sieve is used for the sieving operation, and the diameter of the alloy powder under the sieve is ≤75 μm.

[0020] Specifically, the specific parameters of the ball milling operation in step S4 are: ball-to-material ratio of 1:15-25, rotation speed of 300-500 rpm, and ball milling time of 0.5-2.0 hours; preferably, the ball-to-material ratio is 1:20, the rotation speed is 350 rpm, and the ball milling time is 40 minutes.

[0021] The Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy provided by the present invention has good activation performance and hydrogen absorption and desorption performance through component design and improved preparation process. It can be activated once under the conditions of 30° C. and 3 MPa, with a hydrogen storage capacity of ≥1.69wt.%, a hydrogen absorption platform pressure of ≥0.39MPa, and a hydrogen desorption platform pressure of ≥0.3MPa.

[0022] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0023] 1. The Ti-Fe-Y-Mn-Zr-Co-Zn-based hydrogen storage alloy provided by the present invention is easy to activate, has a high hydrogen storage capacity, and has good hydrogen absorption and desorption performance. The present invention uses chemical modification (formula optimization) to first alloy with rare earth element Y and transition metals Mn, Co, Zn and Zr, thereby reducing the activation conditions of the TiFe alloy and shortening the activation cycle; then the cast sample is ball milled for a short time to improve its microstructure, overcome the disadvantages of the Ti-Fe-based hydrogen storage alloy, retain its advantages, and significantly improve the comprehensive performance of the new hydrogen storage alloy, which will be explained in detail below:

[0024] The present invention adds Zr and Mn elements on the basis of Ti-Fe alloy, and Zr and Mn can form ZrMn2 phase. This intermetallic compound can significantly improve the activation ability and the hydrogen storage capacity; adding a small amount of rare earth Y can significantly improve the activation performance of the alloy under the premise of maintaining the hydrogen absorption capacity, and significantly shorten the incubation time of the alloy activation; the addition of Co and Zn can increase the unit cell volume of the alloy, which can not only improve the activation performance of the alloy, but also maintain the hydrogen storage capacity of the alloy; and the addition of Zn can significantly improve the corrosion resistance of the alloy, and can improve the activation performance of the alloy and the cycle stability of the alloy.

[0025] The present invention improves the activation performance of the alloy to the maximum extent through the synergistic effect of the alloy activation performance of different elements.

[0026] 2. The present invention further improves the performance of the hydrogen storage alloy by improving the microstructure. The cast sample is ball milled for a short time to improve its microstructure, overcome the disadvantages of Ti-Fe-based hydrogen storage alloys, and does not cause a large amount of agglomeration, retaining its advantages; mechanical ball milling significantly reduces the grain size of the alloy and forms a large number of crystal defects, increasing the nucleation points and diffusion channels of hydrogen, further reducing the thermal stability of the hydride and improving the hydrogen absorption and desorption kinetics of the alloy.

[0027] 3. The hydrogen storage alloy provided by the present invention can be activated once under the conditions of 30°C and a hydrogen pressure of 3MPa, with a hydrogen storage capacity ≥1.69wt.%, a hydrogen absorption platform pressure ≥0.39MPa, and a hydrogen release platform pressure ≥0.3MPa.

[0028] 4. The method for preparing hydrogen storage alloy provided by the present invention has readily available raw materials, common equipment, relatively mild process conditions, is easy to operate, and takes a short time, and is suitable for large-scale manufacturing and wide promotion.

[0029] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained through the contents particularly pointed out in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The drawings are only for the purpose of illustrating particular embodiments and are not to be considered limiting of the present invention. Like reference symbols denote like components throughout the drawings.

[0031] Figure 1 XRD diffraction spectra of the cast alloys in Examples 1 to 6;

[0032] Figure 2 The SEM morphology of the ball-milled alloy powders in Examples 1 to 6;

[0033] Figure 3 is the XRD pattern of the ball-milled alloy powder in Examples 1 to 6;

[0034] Figure 4 HRTEM morphology images of the ball-milled alloys in Examples 1 to 6 (the red dotted lines indicate the locations of lattice defects). DETAILED DESCRIPTION

[0035] The preferred embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein the accompanying drawings constitute a part of this application and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not used to limit the scope of the present invention.

[0036] The present invention provides an easily activated Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy, wherein the chemical formula of the hydrogen storage alloy is Ti 1.15 Fe 0.8 Y 0.03 Mn 0.35-x-y-z Zr x Co y Zn z , where x, y, z are atomic ratios, and 0.05≤x≤0.15, 0.02≤y≤0.1, 0.02≤z≤0.1.

[0037] The roles and contents of the above components are determined as follows:

[0038] Ti, Fe: Ti and Fe are the main components of the alloy. The generated TiFe phase is the main phase for hydrogen absorption and desorption reactions. If the proportion is too low, the hydrogen storage capacity of the alloy will be reduced.

[0039] Y: Adding a small amount of rare earth Y can significantly improve the activation performance of the alloy while maintaining the hydrogen absorption capacity, and significantly shorten the incubation time of the alloy activation. This is because rare earth elements easily form rare earth hydrides with hydrogen atoms and become the catalytic active center of the alloy. The optimal value range of the Y atomic ratio is 3-4% of the Fe atomic ratio. Too low an addition will reduce the catalytic effect of Y, while excessive Y will reduce the hydrogen storage capacity of the alloy.

[0040] Zr, Mn: The generated ZrMn2 can participate in the hydrogen absorption and desorption reaction, improve the activation performance of the alloy, and slightly increase the hydrogen storage capacity of the alloy. However, too much ZrMn2 phase will reduce the stability of the alloy's hydrogen absorption and desorption platform pressure, which is not conducive to the application of the alloy.

[0041] Co, Zn: The addition of Co and Zn can increase the unit cell volume of the alloy, which can not only improve the activation performance of the alloy, but also maintain the hydrogen storage capacity of the alloy. The optimal content of Co and Zn is about 1 / 2 of Zr. If the addition amount is too little, the expansion effect of the alloy unit cell volume will be reduced, which is not conducive to improving the activation performance. If the addition amount is too much, the hydrogen storage capacity of the alloy will be greatly reduced.

[0042] Zn: Zn can improve the corrosion resistance of the alloy, thereby improving the cyclic stability of the alloy. At the same time, the addition of Zn can also increase the defect density of the alloy, thereby slightly improving the activation performance of the alloy. However, too much Zn will reduce the hydrogen storage capacity of the alloy.

[0043] From the effects of these elements, we can see that TiFe phase is the main phase of the alloy participating in the hydrogen absorption and desorption reaction. The addition of other elements can improve the activation performance of the alloy, but they also have certain adverse effects. For example, Y, Co, and Zn will reduce the hydrogen storage capacity of the alloy, and Zr and Mn will reduce the stability of the hydrogen absorption and desorption platform pressure. Therefore, in order to ensure the hydrogen storage capacity and platform pressure stability of the alloy, the addition amount of each element must be strictly controlled. After many experiments, it was found that Ti 1.15 Fe 0.8 Y 0.03 Mn 0.35-x-y-z Zr x Co y Zn z The optimal choice of x:y:z is x:y:z=0.1:0.05:0.05.

[0044] Preferably, it is characterized in that x:y:z=0.1:0.05:0.05.

[0045] Specifically, the hydrogen storage alloy includes a multiphase structure, including a TiFe phase and an intermetallic compound ZrMn2 phase, and the proportion of the ZrMn2 phase is 10-15% of the TiFe phase (e.g. Figure 1 As shown in the figure, too much ZrMn2 phase will reduce the stability of the alloy's hydrogen absorption and desorption platform pressure, which is not conducive to the application of the alloy.

[0046] Specifically, Y exists in a free state, and Co and Zn are solid-dissolved in the matrix phase (TiFe phase). Free Y can fully exert its catalytic effect and improve the activation performance of the alloy, and Co and Zn solid-dissolved in the TiFe phase are beneficial to increasing the unit cell volume of the alloy and improving the activation performance.

[0047] Specifically, the hydrogen storage alloy has a nanocrystalline structure, an average grain size of 15 to 35 nm, and a small grain size combined with a large number of crystal defects ( Figure 4 The red dashed line in the middle is the lattice defect position), which helps to reduce the thermal stability of the hydride and improve the hydrogen absorption and desorption kinetics of the alloy.

[0048] The Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy provided by the present invention has good activation performance and hydrogen absorption and desorption performance through component design and improved preparation process. It can be activated once under the conditions of 30° C. and 3 MPa, with a hydrogen storage capacity of ≥1.69wt.%, a hydrogen absorption platform pressure of ≥0.39MPa, and a hydrogen desorption platform pressure of ≥0.3MPa.

[0049] The present invention also discloses a method for preparing the hydrogen storage alloy, comprising the following specific steps:

[0050] S1: The ingredients are prepared according to the preset chemical formula, wherein a certain proportion of the burn loss is added when weighing Mn, Zn and rare earth Y;

[0051] S2: Place the prepared raw materials in a zirconia crucible in order, place the pure iron rod vertically along the crucible wall, place the block rare earth Y at the bottom of the crucible, place the sponge Ti and Zr above the rare earth, and place the electrolytic Mn, Co and Zn on the sponge Ti and Zr;

[0052] S3: After the materials are placed in order, the furnace cover is closed, and after vacuuming, pure argon is filled in as a protective gas and heated to obtain a molten liquid master alloy, which is kept warm in a molten state and poured into a copper casting mold to obtain a master alloy ingot;

[0053] S4: After the master alloy ingot is mechanically crushed and sieved, the alloy powder under the sieve is loaded into a stainless steel ball mill together with stainless steel grinding balls, and then vacuumed and filled with high-purity argon gas. After ball milling in an omnidirectional planetary high-energy ball mill, a ball-milled alloy powder, i.e., the hydrogen storage alloy, is obtained.

[0054] Scientific composition design combined with appropriate ball milling process can obtain alloy powder with special structure, thus making the alloy have excellent activation performance.

[0055] Specifically, the burn-off amount of Mn, Zn and rare earth Y in step S1 is 5% to 10%. Mn, Zn and rare earth Y are easy to volatilize, and certain losses will occur during the batching and heating and melting process. Therefore, a certain burn-off amount needs to be added, generally 5 to 8%, and no more than 10%.

[0056] Specifically, the mass purity of each raw material metal is ≥99.5%.

[0057] Specifically, the specific process and parameters of step S3 are:

[0058] After the furnace cover is closed, vacuum is drawn to 1×10 -2 ~5×10 -5 Pa, fill with pure argon to 0.01-0.1 MPa, the melting temperature is 1500-1650°C, the melting and heat preservation time is 3-10 minutes, and the heat preservation time is preferably 5-8 minutes, for example, 5, 5.5, 6, 6.5, 7, 7.5, 8 minutes, to ensure that each component is fully melted and mixed evenly.

[0059] In the above preparation method, mechanical ball milling is one of the key steps. Mechanical ball milling can greatly reduce the grain size of the alloy. At the same time, it greatly increases the grain boundary and defect density of the alloy, which provides a channel for the rapid diffusion of hydrogen atoms inside the alloy. Therefore, while improving the activation performance, the hydrogen absorption / desorption kinetics of the alloy is significantly improved.

[0060] Specifically, in step S4, a 200-mesh sieve is used for the sieving operation, and the diameter of the alloy powder under the sieve is ≤75 μm. The preparation of alloy particles of this size will not significantly increase the cost and can also prepare for subsequent ball milling.

[0061] Specifically, the specific parameters of the ball milling operation in step S4 are: ball-to-material ratio of 1:15-25, rotation speed of 300-500 rpm, such as 300, 320, 350, 380, 400, 430, 470, 500 rpm, ball milling time of 0.5-2.0 hours, such as 0.5, 1, 1.5, 2 hours; preferably, the ball-to-material ratio is 1:20, the rotation speed is 350 rpm, and the ball milling time is 40 minutes. Under this ball milling parameter, it is possible to prevent excessive amorphous phase from being generated during ball milling, which would damage the hydrogen storage performance of the alloy. At the same time, the size of the alloy particles and grains can be fully reduced, so that the average grain size is maintained at 15-35 nm, thereby improving the activation performance and hydrogen absorption and desorption rate of the alloy.

[0062] The present invention forms a variety of intermetallic compounds by adding a small amount of rare earth element Y and transition metals Mn, Zr, Co and Zn, which significantly increases the activation performance of the alloy. Combined with mechanical ball milling, the grain size of the alloy is significantly reduced, and a large number of crystal defects are formed, which increases the nucleation points and diffusion channels of hydrogen, further reduces the thermal stability of the alloy and improves its hydrogen absorption and desorption kinetics, thereby obtaining a hydrogen storage material with excellent hydrogen absorption and desorption kinetics. The alloy prepared by combining the alloy component design (component optimization) with the ball milling process (microstructure modification) of the present invention has excellent activation performance and fully meets the activation performance requirements of the alloy in practical applications.

[0063] The chemical composition and proportion of the specific embodiment of the present invention are selected as follows:

[0064] Example 1: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.15 Zr 0.1 Co 0.05 Zn 0.05

[0065] Example 2: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.2 Zr 0.05 Co 0.05 Zn 0.05

[0066] Example 3: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.1 Zr 0.15 Co 0.05 Zn0.05

[0067] Example 4: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.1 Zr 0.1 Co 0.1 Zn 0.05

[0068] Example 5: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.18 Zr 0.1 Co 0.05 Zn 0.02

[0069] Example 6: Ti 1.15 Fe 0.8 Y 0.03 Mn 0.1 Zr 0.1 Co 0.05 Zn 0.1

[0070] Comparative Example 1: Ti 1.1 Fe 0.8 Mn 0.2 (Cast)

[0071] According to the chemical formula composition of each embodiment, rare earth metal Y, sponge Ti and Zr, high-purity Fe, electrolytic Mn, Co and Zn are selected. The surface oxide layer of the high-purity iron rod is removed by sandpaper grinding. The rare earth metal Y and electrolytic Mn and Zn are increased by 5-8wt.% of burnout during batching. The technical parameters of each stage are as follows: the vacuum induction melting furnace is evacuated to 1×10 -2 -5×10 -5 Pa; then fill the furnace with 0.01-0.1MPa inert gas argon as protective gas; the temperature during induction heating is 1500-1650℃; the liquid alloy is kept warm in the molten state for 3-10 minutes; the ingot alloy is mechanically crushed and passed through a 200-mesh sieve, and the particle size is about 75μm. The alloy powder is loaded into a stainless steel ball mill together with stainless steel grinding balls, and ball milled for 0.5-2 hours using an omnidirectional planetary ball mill. All process parameters can be appropriately selected within the above range to prepare the hydrogen storage alloy powder described in the patent.

[0072] Therefore, although the present invention only gives a typical embodiment, this embodiment is applicable to preparation methods with different parameters. It is worth emphasizing that all process parameters can be appropriately selected within the above range to prepare the hydrogen storage alloy powder of the present invention.

[0073] Examples 1 to 6

[0074] Process parameters of Example 1: According to the chemical formula Ti 1.15 Fe 0.8 Y 0.03 Mn 0.15 Zr 0.1 Co 0.05 Zn 0.05 , select bulk rare earth metal Y, sponge Ti and Zr, pure Fe, electrolytic Mn, Co and Zn. The purity of these metals is 99.5%. They are weighed according to the chemical dosage ratio, including 437.0 grams of sponge Ti, 72.4 grams of sponge Zr, 354.78 grams of pure Fe, 22.2 grams of rare earth Y, 68.7 grams of electrolytic Mn, 23.4 grams of electrolytic Co, and 27.3 grams of metal Zn. The weighed bulk metal is placed in the zirconia crucible of the medium frequency induction furnace according to the designed process. The pure Fe rod is placed vertically along the crucible wall, the bulk rare earth Y is placed at the bottom of the crucible, the sponge Ti and Zr are placed above the rare earth Y, and the electrolytic Mn, Co and Zn are placed on the sponge Ti and Zr. Then cover the furnace lid and evacuate for about 30 minutes until the vacuum degree is 5×10 -2 Pa, and then fill in high-purity argon protective gas until the gas pressure reaches -0.04MPa, adjust the heating temperature to about 1650℃, melt all the raw metals, and keep the molten liquid metal warm for 5 minutes to make it uniform. Subsequently, inject the evenly mixed liquid metal into a cylindrical copper mold with a diameter of 30mm and a depth of 80mm, cool it to room temperature in the furnace, and then take it out to obtain a master alloy ingot.

[0075] Alloy Ti 1.15 Fe 0.8 Y 0.03 Mn 0.15 Zr 0.1 Co 0.05 Zn 0.05 After the ingot was mechanically crushed and passed through a 200-mesh sieve, 20 grams of the sieved alloy powder and 400 grams of stainless steel grinding balls were weighed and put into a 250-ml stainless steel ball mill jar, which was evacuated and sealed after being filled with high-purity argon gas, and ball-milled in an omnidirectional planetary high-energy ball mill for 40 minutes.

[0076] The raw materials of Examples 2 to 6 and the comparative example were weighed according to the chemical formula, and other preparation process parameters were the same as those of Example 1.

[0077] The phase structure of the as-cast and ball-milled powders was tested by XRD, the morphology and microstructure of the ball-milled alloy particles were observed by high-resolution transmission electron microscopy (HRTEM) and scanning electron microscopy (SEM), and the crystalline state of the alloy was determined by selected area electron diffraction (SAED). The hydrogen absorption activation performance, hydrogen absorption and desorption capacity and kinetics of the alloy powders were tested by fully automatic Sieverts equipment: the hydrogen absorption temperature was 30°C and the initial hydrogen pressure was 3MPa; the desorption temperature was 30°C and the desorption was at 1×10 -4 MPa pressure.

[0078] Table 1 Solid-state hydrogen storage properties of alloys in different embodiments (comparative examples)

[0079]

[0080] Figure 1 The XRD patterns of the cast alloys of Examples 1 to 6 are shown in Figure 1. It can be seen that the addition of rare earth Y and Mn, Zr, Co and Zn for alloying makes the alloy have a multiphase structure. In addition to the main phase TiFe, there is also an intermetallic compound ZrMn2 phase and a free Y phase, while Co and Zn cannot be directly observed in the XRD, indicating that Co and Zn have been dissolved in the TiFe phase. Through XRD refinement, it can be seen that the ZrMn2 phase accounts for 10-15% of the TiFe phase, and the average grain size of the alloy is 15-35nm.

[0081] Figure 2 The SEM morphologies of the ball-milled alloys of Examples 1 to 6 show that the alloy particles are well dispersed after ball milling without obvious agglomeration, indicating that the ball milling parameters defined in the present invention are helpful to improve the hydrogen absorption and desorption performance.

[0082] Figure 3 The XRD patterns of the ball-milled alloys of Examples 1 to 6 show that ball milling significantly broadens the diffraction peaks of the alloys, which is due to the lattice stress and grain refinement generated after ball milling. Due to the broadening of the diffraction peaks, the originally weak Y diffraction peaks are difficult to distinguish.

[0083] Figure 4 The HRTEM morphologies of the ball-milled alloys of Examples 1 to 6 show that the alloys have a nanocrystalline structure with a nanocrystalline size of 15 to 35 nm.

[0084] The above results show that the ball-milled alloy powder has excellent activation properties and high hydrogen absorption capacity. Obviously, the alloy preparation process of the present invention is simple and easy to operate, and is fully suitable for large-scale production. Its performance meets the requirements of hydrogen storage materials for various purposes. Compared with similar alloys at home and abroad, the hydrogen storage performance of the alloy of the present invention has been significantly improved, and it has obvious advantages, especially the activation difficulty is greatly reduced, and the hydrogen absorption and desorption platform is significantly improved and more balanced. Activation can be completed once under the conditions of 30°C and 3MPa, with a hydrogen storage capacity ≥1.69wt.%, a hydrogen absorption platform pressure ≥0.39MPa, and a hydrogen desorption platform pressure ≥0.3MPa.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. An easily activated Ti-Fe-Y-Mn-Zr-Co-Zn based hydrogen storage alloy, characterized in that: The chemical formula of the hydrogen storage alloy is Ti 1.15 Fe 0.8 Y 0.03 Mn 0.35-x-y-z Zr x Co y Zn z , where x, y, z are atomic ratios, and 0.05≤x≤0.15, 0.02≤y≤0.1, 0.02≤z≤0.

1.

2. The hydrogen storage alloy according to claim 1, characterized in that x:y:z=0.1:0.05:0.

05.

3. The hydrogen storage alloy according to claim 1, characterized in that The hydrogen storage alloy comprises a multiphase structure, including a TiFe phase and an intermetallic compound ZrMn2 phase, and the proportion of the ZrMn2 phase is 10-15% of the TiFe phase.

4. The hydrogen storage alloy according to claim 3, characterized in that Y exists in a free state, and Co and Zn are solid dissolved in the TiFe phase.

5. The hydrogen storage alloy according to claim 1, characterized in that The hydrogen storage alloy has a nanocrystalline structure, and the average grain size is 15-35nm.

6. A method for preparing the hydrogen storage alloy according to any one of claims 1 to 5, characterized in that: The specific steps include: S1: The ingredients are prepared according to the preset chemical formula, wherein a certain proportion of the burn loss is added when weighing Mn, Zn and rare earth Y; S2: Place the prepared raw materials in a zirconia crucible in order, place the pure iron rod vertically along the crucible wall, place the block rare earth Y at the bottom of the crucible, place the sponge Ti and Zr above the rare earth, and place the electrolytic Mn, Co and Zn on the sponge Ti and Zr; S3: After the materials are placed in order, the furnace cover is closed, and after vacuuming, pure argon is filled in as a protective gas and heated to obtain a molten liquid master alloy, which is kept warm in a molten state and poured into a copper casting mold to obtain a master alloy ingot; S4: After the master alloy ingot is mechanically crushed and sieved, the alloy powder under the sieve is loaded into a stainless steel ball mill together with stainless steel grinding balls, and then vacuumed and filled with high-purity argon gas. After ball milling in an omnidirectional planetary high-energy ball mill, a ball-milled alloy powder, i.e., the hydrogen storage alloy, is obtained.

7. The preparation method according to claim 6, characterized in that: In step S1, the burn-off amount of Mn, Zn and rare earth Y is 5% to 10%.

8. The preparation method according to claim 6, characterized in that: The specific process and parameters of step S3 are: After the furnace cover is closed, vacuum is drawn to 1×10 -2 ~5×10 -5 Pa, fill with pure argon to 0.01~0.1MPa, melting temperature 1500~1650℃, melting and holding time 3~10 minutes.

9. The preparation method according to claim 6, characterized in that: In step S4, a 200-mesh sieve is used for the sieving operation, and the diameter of the alloy powder under the sieve is ≤75 μm.

10. The preparation method according to claim 6, characterized in that: The specific parameters of the ball milling operation in step S4 are: ball-to-material ratio 1:15-25, rotation speed 300-500 rpm, and ball milling time 0.5-2.0 hours.

Citation Information

Patent Citations

  • Vacuum induction melting method for titanium-containing hydrogen storage alloy

    CN102660698A

  • Ti-Fe-Gd-Mn-Zr-Zn-V-based hydrogen storage alloy easy to activate and preparation method of Ti-Fe-Gd-Mn-Zr-Zn-V-based hydrogen storage alloy

    CN118880111A

  • Hydrogen-absorbing alloy and hydrogen-absorbing alloy electrode

    CN1240837A

  • TiFe HYDROGEN STORAGE ALLOY AND METHOD OF PRODUCING TiFe HYDROGEN STORAGE ALLOY

    JP2014181344A

  • Hydrogen storage alloy and electrode therefrom

    US5738736A

Cited By

  • Ti-Fe-Ce-Mn-Zr-Al-Co based hydrogen storage alloy easy to activate and preparation method thereof

    CN120249772A

  • Rare earth hydrogen storage alloy powder easy to activate and high in charge retention rate and preparation method of rare earth hydrogen storage alloy powder

    CN121109845A